Acupuncture influences multiple diseases by regulating gut microbiota - Xu, Huimin; Luo, Yingzhe; Li, Qiaoqi; Zhu, Hong (Frontiers in Cellular and Infection Microbiology, 2024)
Acupuncture, an important green and side effect-free therapy in traditional Chinese medicine, is widely use both domestically and internationally. Acupuncture can interact with the gut microbiota and influence various diseases, including metabolic diseases, gastrointestinal diseases, mental disorders, nervous system diseases, and other diseases. This review presents a thorough analysis of these interactions and their impacts and examines the alterations in the gut microbiota and the potential clinical outcomes following acupuncture intervention to establish a basis for the future utilization of acupuncture in clinical treatments.